A hybrid energy system based on renewable energy for the electrification of low-income rural communities - Gaslac, Lucero (2018)
Electrification of low-income rural areas that have a limited connection or no access to electrical grids is one of the most demanding challenges in developing countries such as Peru. The international commitment to stop global warming and the reduction in the cost of renewable sources of energy have reduced the prices of fossil fuels in some cases. This has opened the way to the current research which proposes a hybrid energy system (HES) based on the use of renewable sources of energy. Therefore, a renewable electricity system (HRES) was set up at the village of Monte-Catache in the Cajamarca region, which is one of the poorest areas of Peru. Surveys and field studies were used to evaluate the socioeconomic characteristics, availability of renewable energy resources, and energy demand of this region. Potential energy sources were evaluated, and isolated photovoltaic systems with a battery bank were found to be the most appropriate according to the results obtained in the simulation with HOMER. This proposal constitutes an interesting contribution for future energy solutions in isolated and low-income rural areas.